2021
DOI: 10.1007/s12144-021-01350-1
|View full text |Cite
|
Sign up to set email alerts
|

Women and #MeToo in Italy: Internalized sexualization is associated with tolerance of sexual harassment and negative views of the #MeToo movement

Abstract: As a consequence of exposure to sexualized messages, girls and women may internalize the belief that sexual attractiveness to men is an important aspect of their identity. Whereas research on internalized sexualization has mainly focused on its consequences for girls’ well-being and academic outcomes, the present study (N = 222, women, aged 20 to 29) examined whether internalized sexualization is related to sexist attitudes and tolerance of sexual harassment among young women. It also analyzed internalized sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…About men, this research brings novel evidence that the more they tend to share hostile attitudes toward women who defy traditional gender roles, the less they are inclined to participate in the #MeToo movement because they see it as less beneficial for the victims of sexual harassment and for changing the status quo. These results add to previous evidence that hostile sexism toward women is a crucial predictor of tolerance toward sexual harassment [15][16][17], rape myth acceptance [14], and attitudes toward the #MeToo campaign [19,20]. Indeed, we found that hostile sexism affected not only men's attitudes toward #MeToo but also their intentions to participate in the movement actively.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 84%
See 1 more Smart Citation
“…About men, this research brings novel evidence that the more they tend to share hostile attitudes toward women who defy traditional gender roles, the less they are inclined to participate in the #MeToo movement because they see it as less beneficial for the victims of sexual harassment and for changing the status quo. These results add to previous evidence that hostile sexism toward women is a crucial predictor of tolerance toward sexual harassment [15][16][17], rape myth acceptance [14], and attitudes toward the #MeToo campaign [19,20]. Indeed, we found that hostile sexism affected not only men's attitudes toward #MeToo but also their intentions to participate in the movement actively.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 84%
“…Importantly for the present contribution, Moscatelli et al [19] found that higher hostile sexism toward women predicted women's higher skepticism toward the allegations made by the victims of the so-called "Weinstein scandal" and more negative views of the #MeToo campaign. Similarly, hostile sexism was associated with more negative beliefs concerning the outcomes of the movement, which in turn were associated with a higher tendency to consider social-sexual behaviors as sexual harassment [6].…”
Section: Ambivalence Toward Women and Men As An Antecedent Of Attitud...mentioning
confidence: 53%
“…In the novel, Maddalena expresses the same sentiment, saying that “non devi avere paura: la storia di una donna è la storia di tutte le donne” (Ardone, 2021: 222). Given that the #MeToo movement received relatively more pushback in Italy than in many other nations (Horowitz, 2017; Moscatelli et al, 2021: 6199–6200) and that some of the negative reactions called to mind the kinds of expectations that Franca Viola and her family thwarted, this connection between past, present, and future is not just theoretical but unfortunately all too real. At the same time, the links between social and legal change are also visible in the present, with Italy passing “the ‘Codice Rosso’ ( Red Code ) law, which aims to reinforce the protection of the victims of sexual and domestic violence,” in 2019 (Moscatelli et al, 2021: 6199).…”
Section: Discussionmentioning
confidence: 99%
“…Failing to recognize the severity of discrimination against women in the workplace may lead men to underestimate the socio-psychological effects of such discrimination and, consequently, to be unlikely to act as allies. Raising men’s awareness may be even more critical since gender biases are not always explicit and overtly hostile and can sometimes appear to be even “justified” (e.g., Glick and Fiske, 2011 ; Moscatelli et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%